Molecular pharmacology of GPCRs. (9th October 2018) - Langmead, Christopher J; Summers, Roger J
Abstract : Linked Articles: This article is part of a themed section on Molecular Pharmacology of GPCRs. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.21/issuetoc